Causes of seasonal and decadal variability in a tropical seagrass seascape (Reunion Island, south western Indian Ocean). (5th January 2017) - Cuvillier, A.; Villeneuve, N.; Cordier, E.; Kolasinski, J.; Maurel, L.; Farnier, N.; Frouin, P.
Abstract: While seagrass meadows are considered as vulnerable or declining habitats worldwide, facing many natural and anthropogenic pressures, the opposite trend is suggested by this study in Reunion Island (Indian Ocean). Located at the benthos-pelagos interface, seagrass beds are critical coastal habitats and can be used as relevant health indicators for larger marine ecosystems or land-sea continuum. In order to determine which are the factors driving seagrass ecosystems health it is essential to quantify their seascape pattern fluctuations. The long-term (over 65 years) and seasonal scale variability was assessed in the monospecific Syringodium isoetifolium seagrass bed seascape at the Ermitage/La Saline fringing reef using aerial photographs and field measurements. Both long-term and short-term scales have been informative and both types of monitoring appear as useful tools for seagrass ecosystem management. Strong variations in seagrass coverage were observed in the 16 rasters analyzed from years 1950–2015, the magnitude order was however similar to the one observed at the recent seasonal scale (up to 2016 m 2 gained or 4863 m 2 lost over few months at site scale). Seascape pattern analysis revealed that physical factors (swell events, cyclones) had a major impact on the ocean-exposed site with varying impact degree depending on frequency, duration and intensity. Biotic (herbivory) or anthropogenic (grubbing, nutrient inputs) factors were also identified to influence the structural shape, fragmentation, or disappearance of seagrass beds. Further work is required to better quantify the effect of each single factor, a difficult task due to their combined expression. At the reef scale, these results showed a positive correlation between seagrass beds and inner reef flat coverage suggesting that common factors drive these highly resilient ecosystems. Graphical abstract: Highlights: Combined study of seasonal and mutltidecadal changes in seascape patterns are useful to identify environmental and anthropogenic factors impacting seagrass beds. Multidecadal analysis of seagrass beds seascape patterns identified long term trends due to anthropogenic disturbances. Seasonal fluctuations of seagrass seascape patterns may be more important than responses to cyclones. Monospecific seagrass beds of Syringodium isoetifolium in Reunion island subject to natural and anthropogenic stresses are highly resilient.